Prarancangan Pabrik Dioktil Ftalat dari Ftalik Anhidrat dan 2-Etil Heksanol dengan kapasitas 30.000 Ton/Tahun - Prihantoro, Ariska; , Ir Nur Hidayati, MT, Ph.D; , Dr. Ahmad M. Fuadi, MT (2016)
The manufacture of dioctyl phthalate from phthalic anhydride and 2-ethyl hexanol with a capacity of 30,000 ton/year was planned to be established in 2020 in the Industry Area of Gresik, East Java. The manufacturer was planned to be established to operate continuously for 330 days per year with an amount of employees as many as 115 people. The stages of dioctyl phthalate through an esterification process is begun with the preparation of the raw material of phthalic anhydride as much as 1724,462 kg/hours and 2-ethyl hexanol as much as 8942,102 kg/hours, continued with the stage of reaction of forming dioctyl phthalate, the neutralize stage, and the stage of purification the product. The reaction of forming dioctyl phthalate is helped by catalysts H2SO4 as much as 9,706 kg/hours using the reactor of Continuous Stirred Tank Reactor (CSTR). The reaction takes place in the phase of liquid-liquid, reversible, exothermic, and non isothermal at temperature of 150ᵒC and pressure of 1 atm. To support the process of production, the supporting unit of process or utilities is needed to establish comprising a unit of water supply as much as 181.353,18 kg/hours, the electricity needed is as much as 569,739 kW, the compressed air is as much as 150 m3/hours, and the needs of fuel as much as 813,827 liters/hours as well as laboratory. From the economic analysis conducted to this manufacturer with a fixed capital as much as IDR 88.024.356.791 and the working capital as much as IDR 152.158.129.394, it obtains Return of Investment (ROI) before tax as much as 23,3% and after tax as much as 17,5%. Meanwhile, Pay Out Time (POT) before and after tax are 3,93 years and 24,64 years. Break Event Point and Shut Down Point are as much as 54,43% and 22,02%. For Internal Rate of Return based on DCF is counted as much as 18,3%. Based on the calculation of the economic analysis, it can be concluded that this manufacturer is reasonable to establish